Epidemiological characterization of gestational syphilis cases in the state of Pernambuco, Brazil (Research, Society and Development, 2022)
Objective: to trace the epidemiological profile of cases of gestational syphilis in the state of Pernambuco, from 2015 to 2020. Methodology: This is an epidemiological, retrospective, descriptive study with a quantitative approach on gestational syphilis in the state of Pernambuco. Data collection took place from March to April 2022 through access to the Notifiable Diseases Information System (SINAN), a database linked to the Department of Informatics of the Unified Health System (DATASUS). Results: A notification of 12,401 cases of gestational syphilis was observed in the state, with a predominance of women between 20-39 years old (72.6%), of mixed race (66.9%), with incomplete elementary education (32.3 %). The non-treponemal tests were the most used, compared to the non-treponemal tests, noting that despite primary syphilis being the predominant one, there was no notification of a good part of this variable. Conclusion: It was evidenced that gestational syphilis is a public health problem in the state, and that it has been increasing over time, any errors at the time of notification is configured as a real problem to combat it.